2009
DOI: 10.1590/s0102-311x2009000400003
|View full text |Cite
|
Sign up to set email alerts
|

Tendências da epidemia de AIDS entre subgrupos sob maior risco no Brasil, 1980-2004

Abstract: O presente trabalho tem por objetivo apresentar as tendências da epidemia de AIDS em grupos populacionais sob maior risco no Brasil. A técnica de análise discriminante foi utilizada para reclassificação dos casos masculinos com categoria de exposição ignorada em um dos três grupos homens que fazem sexo com homens (HSH), usuários de drogas injetáveis (UDI) ou heterossexuais. Foram estimadas as taxas de incidência de AIDS por sexo e categoria de exposição no período 1980-2004. No período 1980-1988, os casos homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0
19

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 16 publications
(10 reference statements)
2
30
0
19
Order By: Relevance
“…MSM have the highest HIV prevalence of any population group in Brazil (14%) ranging from 5 to 24% in different regions of the country 1 . This represents a rate 13 times higher than that of heterosexual men 1,2,3 . Moreover, 29% of reported AIDS cases in the country occur among MSM, with nearly 40% in young adults (15 and 24 years) 1,2 .…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…MSM have the highest HIV prevalence of any population group in Brazil (14%) ranging from 5 to 24% in different regions of the country 1 . This represents a rate 13 times higher than that of heterosexual men 1,2,3 . Moreover, 29% of reported AIDS cases in the country occur among MSM, with nearly 40% in young adults (15 and 24 years) 1,2 .…”
Section: Introductionmentioning
confidence: 67%
“…The region presents the worst indicators for prevention and, at the same time, highest rates of risk factors for HIV infection, such as a higher percentage of unprotected sex, little routine HIV testing and difficult access to health services. Surveillance of the epidemic in this area of the country, especially among the most vulnerable groups, and knowledge of the causes of low rates of testing is a priority 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, when the epidemic of HIV/AIDS emerged it was restricted to metropolitan areas in the southeast and south of the country, and its most prevalent transmission was among men who have sex with men, through blood transfusion and intravenous drug use 2 . Currently, the profile of HIV/AIDS has changed, since studies have shown an increase in the number of cases among women 3 , heterosexuals 4 , people between 15 and 24 years old, adults over 50 years old, individuals with low level of education, i.e., pauperization, with the education 5 as a socioeconomic indicator, and an increased number of cases in the less urbanized regions 6 . Today, Antiretroviral Treatment (HAART) is a reality and by 2013, in countries of medium and low income, 11.7 million people received it, and according to current trends, the number will increase to 15 million in 2015 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Apesar disso, a subnotificação de óbitos por hepatite B pode ocorrer, principalmente, nas regiões brasileiras menos favorecidas, pela dificuldade de acesso ao diagnóstico e pela não codificação dessa doença na declaração de óbito. O predomínio do sexo masculino na mortalidade proporcional e o aumento da TAPVP neste sexo podem sugerir maior exposição deste grupo ao vírus, possivelmente em virtude do maior uso de drogas injetáveis 27 , porém outros estudos são necessários para investigar tais hipóteses nesta população. Provavelmente, a infecção pelo VHB vem ocorrendo em faixas etárias mais precoces, levando-se em conta que o óbito por hepatite B é um evento tardio 28 .…”
Section: Introductionunclassified